Chronic disease prevalence in women and air pollution — A 30-year longitudinal cohort study. (July 2015) - To, Teresa; Zhu, Jingqin; Villeneuve, Paul J.; Simatovic, Jacqueline; Feldman, Laura; Gao, Chenwei; Williams, Devon; Chen, Hong; Weichenthal, Scott; Wall, Claus; Miller, Anthony B.
Abstract: Background: Air pollution, such as fine particulate matter (PM2.5 ), can increase risk of adverse health events among people with heart disease, diabetes, asthma and chronic obstructive pulmonary disease (COPD) by aggravating these conditions. Identifying the influence of PM2.5 on prevalence of these conditions may help target interventions to reduce disease morbidity among high-risk populations. Objectives: The objective of this study is to measure the association of exposure of PM2.5 with prevalence risk of various chronic diseases among a longitudinal cohort of women. Methods: Women from Ontario who enrolled in the Canadian National Breast Screening Study (CNBSS) from 1980 to 1985 (n = 29, 549) were linked to provincial health administrative data from April 1, 1992 to March 31, 2013 to determine the prevalence of major chronic disease and conditions (heart disease, diabetes, asthma, COPD, acute myocardial infarction, angina, stroke and cancers). Exposure to PM2.5 was measured using satellite data collected from January 1, 1998 to December 31, 2006 and assigned to resident postal-code at time of entry into study. Poisson regression models were used to describe the relationship between exposure to ambient PM2.5 and chronic disease prevalence. Prevalence rate ratios (PRs) were estimated while adjusting for potential confounders: baseline age, smoking, BMI, marital status, education and occupation. Separate models were run for each chronic disease and condition. Results: Congestive heart failure (PR = 1.31, 95% CI: 1.13, 1.51), diabetes (PR = 1.28, 95% CI: 1.16, 1.41), ischemic heart disease (PR = 1.22, 95% CI: 1.14, 1.30), and stroke (PR = 1.21, 95% CI: 1.09, 1.35) showed over a 20% increase in PRs per 10 μg/m 3 increase in PM2.5 after adjusting for risk factors. Risks were elevated in smokers and those with BMI greater than 30. Conclusions: This study estimated significant elevated prevalent rate ratios per unit increase in PM2.5 in nine of the ten chronic diseases studied. Highlights: We examine the association of PM2.5 exposure with prevalence of major chronic diseases in women. Cumulative PM2.5 data were collected from satellite-based estimates of surface concentrations. Increased exposure increases risk of cancer, diabetes, and cardiovascular and respiratory diseases. The effect of PM2.5 exposure and disease prevalence was markedly larger in smokers and obese women.